Surface-Enhanced Raman Spectroscopy Substrates: Plasmonic Metals to Graphene - Mhlanga, Nikiwe; Ntho, Thabang A.; Chauke, Hleko; Sikhwivhilu, Lucky (Frontiers in Chemistry, 2022)
Surface-Enhanced Raman spectroscopy (SERS), a marvel that uses surfaces to enhance conventional Raman signals, is proposed for a myriad of applications such as diagnosis of diseases, pollutants, and many more. The substrates determine the SERS enhancement and plasmonic metallic nanoparticles such as Au, Ag and Cu have dominated the field. However, the last decades have failed to translate SERS prototypes into real-life applications. Irreproducibility on the SERS signal that stems from the roughened SERS substrates is the main causative factor for this observation. To mitigate irreproducibility several 2-dimensional (2-D) substrates have been sought for use as possible alternatives. Application of 2-D, graphene substrates in Raman renders graphene-enhanced Raman spectroscopy (GERS). This account used density functional theory (DFT) substantiated with experimental Raman to compare the enhancement capabilities of Plasmonic Au nanoparticles (SERS), graphene substrate (GERS) and coupling of the two SERS and GERS substrates. The DFT also enabled the study of the SERS and GERS systems molecular orbital to gain insight into the SERS and GERS mechanisms. The amalgamation of the SERS and GERS occurrence, i.e., graphene doped with Plasmonic metallic substrates showed a pronounced enhancement and matched the Au-driven enhancement emanating from both electromagnetic and charge transfer SERS and GERS mechanisms.